Support services for international university students : an Australian case study - Roberts, Pamela A. (Curtin University, 2011)
The purpose of this study was to contribute to an improved understanding of international students’ support needs by identifying the issues that are significant to students in terms of their study experience, the services they consider as valuable and the factors that contribute to the degree to which those services are taken up. Included within the parameters of this study is a review of the background development of international education from a global and national perspective and the legislative and governing frameworks which impact on educational institutions that provide courses of study to international students. This is followed by a review of the literature in relation to international student experiences as regard the culture of support, adjustment issues and support service provision and utilisation.The research was undertaken in one university with a long history of enrolling international students in courses of study in Australia. The university has a corporatised model of operations with a strong emphasis on meeting strategic targets and ‘balanced scorecard’ outcomes. In 2010 10, 702 international students were enrolled onshore in the education institution across various programs of study and these students account for close to 25% of the institution’s total onshore student population. Within the setting, support services are provided in accordance with the legislated requirements for education providers in Australia. Utilisation of services within the university is variable and no research exists which had examined in any depth the culture of support service provision, student awareness, use, access, perceived importance and barriers to use of services.A three stage research process was used to examine the phenomena, involving interviews with key support service providers in the university, focus groups with international students and a subsequent survey, to which 395 international students responded. The majority of international students were of the view that the range of support services provided was appropriate and met their needs. There was clear evidence however that the current services needed to be improved and that a more student centred focus was crucial to ensure services were provided in a way which was useful. Issues raised as influencing use of services by international students included the culture, importance, awareness, quality of information, access, timeliness and cost.One overarching recommendation is made and associated implementation strategies proposed, both related to the future management and direction of support and support services delivery in the university. Central to the recommendation is the need to implement a student centred model of support and support service delivery within the university. As set out in the conceptual model developed, the critical elements needed to support this approach include the need to: conduct a review of the current services to ensure they are provided in a way which is useful to students, design a quality framework for the delivery of services which includes the coordination, delivery and ongoing management and monitoring of services, review strategic plans and identify organisational learning needs to facilitate development of the student centred model of support service delivery.